Teachers' Adaptive Learning Strategies for Children with ADHD Symptoms - Vina, Dhea Alfa; Jayati, Endah Luluk Dwi; Sholikhah, Mar’atus; Elvira, Melly (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3583, 2025)
Early childhood with Attention Deficit Hyperactivity Disorder (ADHD) symptoms requires a tailored learning approach because they have difficulty maintaining attention, controlling impulses, and following instructions consistently. This condition requires teachers to implement adaptive learning strategies that can accommodate the children's individual needs. This study aims to analyze the adaptive learning strategies used by teachers to recognize distraction patterns and manage the behavior of children with ADHD symptoms at ABA 01 Batu Kindergarten. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews with teachers and the principal, observations of classroom interactions, and supporting documentation. The analysis was conducted using thematic analysis through a coding process to identify strategic patterns that emerged in learning practices. The results of the study showed that teachers implemented adaptive strategies in several forms: (1) short, clear, and repeated instructions to help children understand directions; (2) positive reinforcement in the form of praise and rewards as motivation and behavioral regulation; (3) adjusting the rhythm and structure of activities, such as providing breaks, motor activities, and dividing tasks into small steps so that children do not become distracted quickly; (4) an empathetic emotional approach, where teachers build a sense of security through patience, closeness, and sensitive responses to changes in children's emotions; (5) arranging a learning environment with minimal distractions; and (6) collaboration with parents to align parenting patterns, behavioral regulation, and reinforcement at home. However, the implementation of the strategy still faces obstacles in the form of limited expert staff, parental consistency, and the less than optimal use of supporting visual media. In conclusion, adaptive learning strategies that are responsive, flexible, and based on empathy are key to supporting the learning engagement of children with ADHD. This approach allows teachers to more effectively direct children's behavior and foster optimal development.